Pengaruh Disiplin Dan Semangat Kerja Terhadap Produktivitas Kerja Guru Madrasah Aliyah Negeri Banggai: Influence Discipline and Work Morale on Work Productivity of Banggai State Madrasah Aliyah Teachers - Kamaru, Sri Mulyaningsih; Ladjiham, Maya Anghita; Landahim, Asrikal (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
This research was conducted to determine and analyze the influence of discipline and work enthusiasm on the work productivity of Banggai State Madrasah Aliyah teachers. The analytical method used in this research is multiple linear regression analysis using 45 samples. Based on the results of data processing with the help of the SPSS version 25 program, the multiple linear regression equation Y = 0.968 + 0.026X1 + 0.761X2 + e was obtained. The constant value is 0.968, meaning that if it is not controlled by the discipline and work enthusiasm variables, productivity is 0.968. The variables discipline (X1), work enthusiasm (X2) have a significant and positive influence on work productivity (Y). The coefficient of determination (R) is 0.844 or is in the interval 0.80 – 1.00, meaning that the relationship between the independent variables, discipline and work enthusiasm, has a strong relationship with the dependent variable, work productivity. The coefficient of determination (R2) of 0.712 or 71.2% shows the percentage of influence or contribution of the independent variable in explaining the dependent variable, namely 71.2% and the rest is explained by variables other than the variables being tested. The results of the F test show that the variables of discipline and work enthusiasm have a significant and positive effect on work productivity with an Fcount of 2.019 and a Ftable of 3.23.